State Defense Force Monograph Series. Winter 2005, Homeland Security - Tulak, Arthur N.; Kraft, R. W.; Silbaugh, Don; Bankus, Brent C.; Coulombe, Andre N.; Hershkowitz, Martin; Wardell, Jr, Herbert O. (2005)
Contents of this monograph is as follows: 1) State Defense Forces: "Forces for" NORTHCOM and Homeland Security? 2) State Defense Forces, an Untapped Homeland Defense Asset; 3) The State Guard Experience and Homeland Defense; and 4) A Guide for Establishing a State Defense Force with a Homeland Security Mission. The original document contains color images. Published in State Defense Force Monograph Series: Homeland Security, p3-72, Winter 2005.